CONSERVATIVE ORTHOPEDIC TREATMENT OF RHEUMATIC DISEASES: RHEUMATOID ARTHRITIS, ANKYLOSING SPONDYLITIS, OSTEOARTHROSIS, SOFT TISSUE DISEASES (PART II) - V P Pavlov (Современная ревматология)
Part II of the paper completes the section on medical measures for rheumatoid arthritis and outlines the principles of conservative orthopedic treatment of rheumatic diseases: ankylosing spondylitis, osteorthrosis, and soft tissue diseases.